Dynamic wrinkling pattern exhibiting tunable fluorescence for anticounterfeiting applications - Ma, Tianjiao; Li, Tiantian; Zhou, Liangwei; Ma, Xiaodong; Yin, Jie; Jiang, Xuesong (Nature communications, 2020)
A dynamic surface pattern with a topography and fluorescence in response to environmental stimulus can enable information recording, hiding, and reading. Such patterns are therefore widely used in information security and anticounterfeiting. Here, we demonstrate a dynamic dual pattern using a supramolecular network comprising a copolymer containing pyridine (P4VP-nBA-S) and hydroxyl distyrylpyridine (DSP-OH) as the skin layer for bilayer wrinkling systems, in which both the wrinkle morphology and fluorescence color can be simultaneously regulated by visible light-triggered isomerization of DSP-OH, or acids. Acid-induced protonation of pyridines can dynamically regulate the cross-linking of the skin layer through hydrogen bonding, and the fluorescence of DSP-OH. On selective irradiation with 450 nm visible light or acid treatment, the resulting hierarchical patterned surface becomes smooth and wrinkled reversibly, and simultaneously its fluorescence changes dynamically from blue to orange-red. The smart surfaces with dynamic hierarchical wrinkles and fluorescence can find potential application in anticounterfeiting. Dynamic surface patterns are widely used in information security and anticounterfeiting technologies. Here, the authors demonstrated a dynamic wrinkled and fluorescent pattern using a supramolecular network in which both the wrinkle morphology and fluorescence color can be regulated by pH or light.